(untitled) (Brazilian Geographical Journal, 2011)
The objective of this study was to evaluate the performance of native species in a reforestation process carried out on the headwaters of a stream Clemências, in Quirinópolis, GO. It was measured the height, diameter at the soil surface of the planted area and the percentage of mortality of the species planted in there. A high mortality was observed, which may be connected with the absence of a correct management in the place, particularly with the crown in the locality of the seedlings, and also to a prolonged drought. Cecropia pachystachya, Jacaranda cuspidifolia, Clitorea fairchildiana, Enterolobium contortisiliquum, Leucaena leucocephala e Dipteryx alata, had higher survival rates, therefore they are recommended to use in reforestation of degraded areas. Most species suffered a drastic reduction in their vegetation cover in the dry season, indicating that the loss of their leaves can be an escape mechanism because of the water stress.